2019
DOI: 10.1111/tbed.13300
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological factors and mitigation measures influencing production losses in cattle due to bovine viral diarrhoea virus infection: A meta‐analysis

Abstract: Infection with bovine viral diarrhoea virus (BVDV) is associated with a loss in productivity in cattle farms. Determining which factors influence monetary losses due to BVDV could facilitate the implementation of mitigation measures to reduce the burden of BVDV. Mixed‐effect meta‐analysis models were performed to estimate the extent to which the costs of mean annual BVDV production losses per animal may be influenced by epidemiological factors such as BVDV introduction risk, initial prevalence, viral circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 32 publications
1
38
0
1
Order By: Relevance
“…In the present study, some of these were initially identified as risk factors with independent Chi-square tests (e.g., the existence of corrals in the farm, and use of mechanical milking), although none of them were significant under the multivariate logistic regression analysis. The large heterogeneity of epidemiological and mitigation factors among BVDV studies might be attributed to different modeling approaches and to the omission of covariates such as herd immunity, management practices, age of animals, stocking rate, and community pasturing activities [ 30 ], which are of remarkable importance in pasture-based systems, the predominant cattle farming strategy in the South American region.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, some of these were initially identified as risk factors with independent Chi-square tests (e.g., the existence of corrals in the farm, and use of mechanical milking), although none of them were significant under the multivariate logistic regression analysis. The large heterogeneity of epidemiological and mitigation factors among BVDV studies might be attributed to different modeling approaches and to the omission of covariates such as herd immunity, management practices, age of animals, stocking rate, and community pasturing activities [ 30 ], which are of remarkable importance in pasture-based systems, the predominant cattle farming strategy in the South American region.…”
Section: Discussionmentioning
confidence: 99%
“…32 Therefore, farmers need to be motivated both to change existing behaviours and to implement effective biosecurity practices to reduce the risk of disease introduction. [33][34][35] MCA and TSCA show that there are three main farm typologies in relation to the implementation of biosecurity measures differentiated mainly by region (which implies different implementation of BVDV and BoHV-1 control programmes) and herd size. Although some biosecurity limitations were common, others were more specific to each cluster, similar to the observation made by Sarrazin and others.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine pestiviruses are an important group of pathogens that cause significant economic losses to the cattle industry worldwide [ 19 ]. BVD is well recognised as an economic factor of cattle production in the western world but less so in the developing world including emerging economies, such as Brazil, where it is not yet considered in disease control programmes.…”
Section: Impact and Control Of Bovine Pestivirusesmentioning
confidence: 99%